Die Reform des Morbi-RSA durch das Gesetz für einen fairen Kassenwettbewerb in der gesetzlichen Krankenversicherung (GKVFKG) : Einschätzung des Beitrags zur Minderung von Wettbewerbsverzerrungen - Moska Kohsar (2021)
Introduction The morbidity based risk adjustment (Morbi-RSA) in the German health insurance system makes sure that risk selection is avoided and fair competitive conditions are given to health insurance companies. The current framing of the Morbi-RSA only partially meets those goals which cause unequal treatment of health insurance companies relating to the competition. For this reason, a law to reform the Morbi-RSA has been implemented thus compromises several measures for further development of the Morbi-RSA. This study aimed to examine whether measures by law can reduce existing distortions of competition among the health insurance companies. Methods To answer this question a qualitative document analysis is being used. The first step is to analyze statements regarding the measures by law. Also, interviews with health care experts are being performed. The interviews are based on generated guidelines. In a final step, the data is interpreted by using qualitative content analysis according to German psychologist Mayring. Results A total of seven statements were identified, analyzed, and two interviews with health care experts were performed. Due to different argumentation and assessment, comparison and weighing of the measures was complex. Most of the measures can be considered as effective to reduce distortions of competition. However, the deletion of the EMR is not substantiated. Conclusion In summary, the measures can provide fair competition among the health insurance companies and reduce the distortion in the Morbi-RSA system. The actual effects of the measures remain to be seen.
Keywords: morbidity-based risk adjustment; German health care reform; competition; Morbi-RSA; Kassenwettbewerb; GKV-FKG; Gesundheitsreform